Design and development of an innovative "GAMAT" oil bottle or dispenser - Norsofea Aida Binti Abdul Gani (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
"Gamat" is a marine life that usually lives in the crack of the rocks. It is able to cure many diseases. Because of that, "Gamat" oil has been produced and bottled in treating minor injuries, joint pain and as massge oiil. Problems detected when "Gamat" oil customer find it difficult to open the inner cap oil bottle when they want to use it. The hole should be made in advance to enable the oil to be used. The inner cap has also contributed to the increase in time during the process of filling and bottling the "Gamat" oil.